2011
DOI: 10.1016/j.bcp.2011.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the P2Y1 receptor induces apoptosis and inhibits proliferation of prostate cancer cells

Abstract: G protein-coupled receptors, the largest cell surface receptor family, have emerged as critical players in cell death and survival. High gene expression level of the Gq-coupled P2Y1 nucleotide receptor in PC-3 prostate cancer cells was demonstrated using real-time quantitative PCR and confirmed by Western blotting and confocal laser scanning microscopy. A selective P2Y1 receptor agonist, the ADP analogue MRS2365, concentration-dependently induced intracellular calcium mobilization (EC50 5.28 nM), which was dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
5
32
0
Order By: Relevance
“…Previous studies showed a growth-inhibitory effect of both ATP and adenosine on PCa cells (13,15,16,(31)(32)(33). Corresponding to those findings, a growth-inhibitory effect of ATP and adenosine was observed on various PCa cell lines used in this study, including LNCaP, C4-2, C4-2B, DU145 and PC3, in a dose-dependent manner ( Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies showed a growth-inhibitory effect of both ATP and adenosine on PCa cells (13,15,16,(31)(32)(33). Corresponding to those findings, a growth-inhibitory effect of ATP and adenosine was observed on various PCa cell lines used in this study, including LNCaP, C4-2, C4-2B, DU145 and PC3, in a dose-dependent manner ( Figure 1).…”
Section: Discussionsupporting
confidence: 88%
“…Figure 4a shows that NECA (1 μM) decreases CHX-induced LDH release. It has been shown previously that the selective P2Y 1 receptor agonist MRS2365 (1 μM) enhanced the effect of CHX to promote LDH release in PC-3 cells [4]. Here, we have shown that the MRS2365-induced enhancement of CHXinduced LDH release was also diminished by NECA (Fig.…”
Section: Resultssupporting
confidence: 71%
“…In addition to the high expression level of the A 2B AR, P2Y 1 receptors [4], which are activated by endogenous adenine nucleotides, and ectonucleotidases CD39 and CD73 [19], which together degrade adenine nucleotides to produce adenosine, are also abundantly expressed in prostate cancer cells. Stagg et al [20] recently reported that CD73 deficiency suppressed prostate tumorigenesis in a mouse transgenic model of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations